PEMILIHAN E-MARKETPLACE BAGI PEDAGANG BATIK PEKALONGAN MENGGUNAKAN METODE FUZZY AHP-TOPSIS - Nur Ika Royanti; Era Yunianto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Nowadays Pekalongan batik traders have adopted electronic marketing using e- marketplace. The quality of an e-marketplace affects the number of customers who  decide  to  shop  through  the  e-marketplace.  Dimensions  that  affect  the quality of an e-marketplace include service quality, system quality, information quality and vendor-specific quality. In this study, the e-marketplace for Pekalongan batik traders will be chosen as an effort to expand market access using the integration of fuzzy AHP and fuzzy TOPSIS methods. In collecting data using a questionnaire given to Pekalongan batik traders. The results of the study showed that the service quality criteria had a weight of 28.4%, the system quality criteria had a weight of 23.1%, the information quality criteria had a weight of 25.1% and the vendor specific quality criteria had a weight of 23.4%. Alternate ranking sequences are TP (CC 0.7543), LAZ (CC 0.07535) and BL (CC 0.07281). The results of this study are expected to be a recommendation for Pekalongan  batik  traders  in  the  selection  of  e-marketplace  as  a  market expansion   effort   and   for   e-marketplace   developers   in   determining   e- marketplace development strategies Keywords: Fuzzy AHP, Fuzzy TOPSIS, e-marketplace